Did the minority Gillard government keep its promises? A study of promissory representation in Australia. Issue 2 (3rd April 2019) - Carson, Andrea; Gibbons, Andrew; Martin, Aaron
ABSTRACT: When the Gillard government formed a minority government in 2010 many commentators argued that the government would be unable to fulfil its mandate. Despite this, the Gillard government was able to pass a record amount of legislation – comparable to previous majority-led governments – suggesting the government was effective at negotiating legislative passage. Less understood is whether the Gillard government was able to keep its election promises given the constraints of minority government. This is an important empirical and normative question. In their most basic form elections are designed to allow the public to hold politicians and political parties to account for their past performance. Central to this is whether parties have fulfilled the promises they made at the previous election. But how do parties express election promises to citizens and are they likely to fulfil these promises? Does minority government status make a difference? We examine these questions in the first contemporary Australian study of promise fulfilment, examining promises made and promise fulfilment of the Gillard minority government (2010–2013). We adopt the methods of the Comparative Party Pledges Project (CPPP). Consistent with the international literature, we find that the Gillard government fulfilled most of its election promises suggesting minority government status did not have a large effect on promise fulfilment.